Reduction of the energy consumption from goods transport in cities: Summary of the project - Dorn-Jensen, Henrik (Proceedings from the Annual Transport Conference at Aalborg University, 1995)
This summary contains the most important results of a research project about goods transport in cities. In the project the consequences of establishing a city distribution terminal have been analysed on the basis of the Danish city Odense with 140,000 inhabitants. The project has recieved support from the SAVE Programme, which is a programme supporting research in saving energy within several fields, among these transportation planning. The SAVE Programme is financed by the European Commission. The support has amounted to 92,250 ECU. The project has furthermore recieved support from the Danish Transport Council. This support has amounted to 430,000 Danish kroner, or approximately 56,000 ECU.